Extended life-span conferred by cotransporter gene mutations in Drosophila. - Rogina, B.; Reenan, R.A.; Nilsen, S.P.; Helfand, S.L. (Science, 2000)
Aging is genetically determined and environmentally modulated. In a study of longevity in the adult fruit fly, Drosophila melanogaster, we found that five independent P-element insertional mutations in a single gene resulted in a near doubling of the average adult life-span without a decline in fertility or physical activity. Sequence analysis revealed that the product of this gene, named Indy (for I'm not dead yet), is most closely related to a mammalian sodium dicarboxylate cotransporter-a membrane protein that transports Krebs cycle intermediates. Indy was most abundantly expressed in the fat body, midgut, and oenocytes: the principal sites of intermediary metabolism in the fly. Excision of the P element resulted in a reversion to normal life-span. These mutations may create a metabolic state that mimics caloric restriction, which has been shown to extend life-span.